Looking back through the MIST: a perspective of evolving strategies and key focus areas for metabolite safety analysis. (July 2010) - Nedderman, Angus NR; Wright, Pat
The publication of the US FDA MIST guidance document in 2008 reignited the debate around the most appropriate strategies to underwrite metabolite safety for novel compounds. Whilst some organizations have suggested that the guidelines necessitate a paradigm shift to more thorough metabolite analysis during early development, an evaluation of historical practices shows that the principles of the guidelines have always largely underpinned metabolism studies within the pharmaceutical industry. Therefore, it is argued that existing practices, when coupled to appropriate emerging analytical tools and a case-by-case consideration of the relevance of the generated metabolism data in terms of structure, physicochemisty, abundance and activity, represent a fit-for-purpose approach to metabolite-safety assessments.